Strategi Manajemen Pemasaran Berdasarkan Tata Letak Penjualan pada Car Free Day di Kabupaten Bone - Hamjan, Andi Lisa Aryani; Widya Astuti; Jumardi, Jumardi; Angger Bulan; Otong Karyono (Pusat Riset dan Inovasi Nasional, 2026)
The Car Free Day (CFD) program in Bone Regency has evolved into a dynamic economic space that requires micro-entrepreneurs to implement effective marketing management strategies. This study aims to analyze the implementation of marketing strategies based on sales layout applied by street vendors during CFD activities. A descriptive qualitative approach was employed through observations and in-depth interviews with eight vendors representing various product categories. The findings reveal that stall layout serves as the primary determinant influencing customer accessibility, visitor flow, and product visibility, which directly affects sales performance. Vendors also focus on maintaining product quality, setting stable and competitive prices, and utilizing simple promotional methods through direct interaction to build strong customer relationships. Moreover, government zoning policies provide spatial stability for vendors, although they limit the flexibility to change locations. The study concludes that marketing strategies in CFD Bone are shaped by the utilization of temporary public spaces that combine economic and social dynamics. Recommendations include optimizing stall layout, enhancing hygiene, strengthening product innovation, and increasing the use of digital platforms to boost the competitiveness of micro-enterprises within CFD activities.